Match characteristics of professional European male table tennis players - Djokic, Z.; Munivrana, G.; Levajac, D. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The purpose of this study was to investigate the match characteristics of professional male table tennis players considering analyses of men`s singles competition at the 2015 European Games held in Baku Methods: Forty five players which were competing in Men`s individual event at EG 2015 in 46 matches were analysed. Match characteristics were also analysed according of the phase of competition (from the 1st round to final) and considering the performance level of players. Performance indicators were: played points, games, set and match duration, the number of strokes in point (average and longest rallies). From these observations, the proportion of match time spent in play (effective playing time of whole match and sets) was determined. For all indicators descriptive statistical parameters were calculated, while differences according phase of competition and performance level of players were analysed using one-way ANOVA (p<0.05). Results: Players played average 101.07±22.34 points per game (best of seven) and 18.2±1.00 points per set. Points in the game and sets were increasing during the playing from stage to stage. Mean strokes per point (rally) was 4.76±1.64, and longest rallies in games were 9.37±3.75. Total match time in competition was 35.0±6.1 min (in range, from 28.0-46.0 min) and it was increased from stage to stage. Duration of played set was 6.07±0.7 min (4.8-7.7 min). In all analysed performance indicators according of the phase of competition statistically significant differences were noted (p<0.05). These results provide original information about the match characteristics which can be used in modelling of the training process.